Ancient China - Atkins, Marcie Flinchum (Minneapolis, Minnesota : Essential Library, an imprint of Abdo Publishing, 2015)
"In Ancient China, readers discover the history and impressive accomplishments of the people of ancient China, including their technological wonders and feats of construction. Engaging text provides details on the civilizations history, development, daily life, culture, art, technology, warfare, social organization, and more." -- Publishers website.
Keywords: Civilization; Manners and customs; China -- Civilization -- To 221 B.C.; Juvenile literature; China -- Civilization -- 221 B.C.-960 A.D.; Juvenile literature; Literature